PEMERINGKATAN BANK DI INDONESIA DENGAN MENGGUNAKAN ANALISIS RASIO KEUANGAN (STUDI EMPIRIS PADA BANK DENGAN KELOMPOK MODAL DI ATAS 1 TRILIUN) - Hermawan Budi Prasetiyo; Hafidza Nash'ul Amrina (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
The purpose of this research is to give the descriptive discourse about the rating of bank in Indonesia using financial ratios base on capital bank group over 1 trillion at observations in 2007-2008. This research is use five kinds of ratios i.e. capital ratio, productive assets ratio, profitability ratio, liquidity ratio, and efficiency, ratio which comprises nine financial ratios as it has been researched by Info Bank (2006). The data which is used in this research is secondary data; it is obtained from Bank Indonesia, which in the form of financial reporting data. The results found that 40 banks have a very good predicate, 3 banks have a good predicate, and 1 bank has an enough predicate. Besides that, the results also found that a large capital can not guarantee the financial ratios quality.